« Une jeune femme, en robe de mérinos bleu... » - Florence Pellegrini (Flaubert: Revue Critique et Génétique)
Based on the analysis of the first meeting scenes in two film adaptations of Madame Bovary — Claude Chabrol’s film with Isabelle Huppert (1991) and Sophie Barthes’ film with Mia Wasikowska (2014) — this article sets out to highlight the recomposition of the heroine they propose, as well as the reconfiguration of plot and narrative stakes.